Influences of high-heeled shoe parameters on gait cycle, center of pressure trajectory, and plantar pressure in young females during treadmill walking. (8th May 2020) - Shang, Jiangyinzi; Geng, Xiang; Wang, Chen; Chen, Li; Zhang, Chao; Huang, Jiazhang; Wang, Xu; Yan, Alan; Ma, Xin
Purpose: This study aimed to investigate the influences of high-heeled shoe (HHS) parameters on gait cycle, center of pressure (COP) trajectory, and plantar pressure in young females. Methods: Twenty healthy adult females were recruited to participate in this study. Subjects walked on a treadmill at a fixed speed (1 m/s). Overall, six pairs of HHSs were evaluated, presenting two heel types (thin and thick) and three different heel heights (low: 3 cm, medium: 6 cm, and high: 8.2 cm). Subjects also wore flat shoes (heel height: 0.2 cm) as the control group. Results: The gait cycle, COP parameters, peak pressure (PP), maximum force, contact area (CA), and force–time integral (impulse) were measured. The comparison between these parameters when the volunteers wore thick heel and flat shoes at different walking conditions indicated that thin heels caused a significant increase in the pre-swing parameter, CA, and PP of the first toe and first metatarsus. Increased heel heights yielded smaller gait line lengths, single support lines, and smaller hindfoot areas. By contrast, increased anterior–posterior positions and plantar pressure parameter values were noted for the forefoot. Conclusions: Data analyses showed significant differences in the plantar pressure distribution associated with heel height and heel type at increased pressure in the first metatarsal and central forefoot region and decreased pressure in the midfoot and heel sections, thus increasing anterior shift. The results presented herein may allow for the design of HHSs with reduced adverse health effects on the wearer.